HUMANISM and TESOL - Wisda Ramadhani Robi’ah; Farida Nur Fatinah (Samudra Publisher, 2025)
The humanistic approach in language teaching emphasizes the importance of emotional and social aspects, alongside cognitive development, to create a holistic learning environment. This study aims to explore the application of humanistic methods, particularly Community Language Learning (CLL) and Suggestopedia, in teaching English as a Foreign Language (EFL). Using a literature analysis method of academic articles and documents, this research identifies the applications, benefits, and challenges of these approaches. The findings reveal that CLL enhances learners' fluency and confidence through community-based interaction and the teacher’s role as a facilitator. Suggestopedia, on the other hand, frees learners from psychological barriers, fostering creativity, motivation, and emotional well-being. In the context of TESOL, the integration of humanistic principles has been proven to support effective, meaningful, and learner-centered language learning by addressing both emotional and cognitive needs.